A study of neutrophil dysfunction related disorder in Malaysia: A case study on a X-linked chronic granulomatous disease in a male child / Hemahwathy d/o Chanthira Kumar - Chanthira Kumar, Hemahwathy (2014)
Chronic Granulomatous Disease (CGD) is a primary immunodeficiency disease (PID) in which the defect lies at the neutrophil intracellular killing step of the phagocytosis process. It is caused by a dysfunctional respiratory burst enzyme Nicotinamide Adenine Dinucleotide Phosphate (NADPH)-oxidase, a multi-protein complex making CGD a heterogeneous disease. X-linked CGD (X-CGD) is due to a mutation in the CYBB gene that codes for gp91-phox, while autosomal CGD is caused by mutations in genes that code for p22-phox, p47-phox, p67-phox, p40-phox and Rac2. The incidence of Klinefelter’s Syndrome and CGD occurring together is extremely rare. This study describes a family where the youngest male child suffered from X-CGD while his older brother was both an X-CGD carrier and a Klinefelter. Flow cytometry was used to study the respiratory burst and gp91-phox protein expression in neutrophils, while genetic investigations was done by RT-PCR, PCR and X-chromosome short tandem repeat analysis. The Dihydrorhodamine (DHR) assay revealed that the patient’s neutrophils failed to produce a respiratory burst while both the mother and the older brother showed a bimodal response. gp91-phox protein expression mirrored the DHR findings. The patient’s cDNA showed a C>T change at nucleotide 676 of the CYBB gene and similar change was observed in patient’s genomic DNA. The mother and the older brother were heterozygous, with C and T, in this position. The c.676C>T is a nonsense mutation that leads to premature termination of the gp91-phox protein. The brother was karyotyped as 47, XXY and X chromosome analysis revealed that he had inherited both of his mother’s X chromosomes. This study is the first to report concurrence of X-CGD carrier and Klinefelter’s Syndrome in an individual and therefore argues for family members to be included in PID investigations. Keywords: Primary Immunodeficiency Disease, Chronic Granulomatous Disease, Klinefelter’s Syndrome, NADPH-oxidase, gp91-phox protein